A coated platinum-gold catalyst, its preparation method and use

CN122878563APending Publication Date: 2026-10-09SHENZHEN PARKWELLER NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611020450.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0009]为此,本发明所要解决的技术问题在于现有包覆型铂金催化剂释放温度可调性差、存储稳定性不佳,与有机硅基体相容性差、抗析出稳定性不足,从而提出一种室温温度可调、稳定性高、相容性好、抗析出性能优异的包覆型铂金催化剂及其制备方法与应用

Benefits of technology

本发明提供的包覆型铂金催化剂,包括:芯材和包覆于芯材外部的壳层,其中,芯材包括卡斯特铂金催化剂和抑制剂,包覆型铂金催化剂中,卡斯特铂金催化剂的浓度为1000-5000ppm,抑制剂的浓度为50-150ppm;壳层为有机-无机杂化网络,有机-无机杂化网络由正硅酸乙酯、聚己内酯二醇、乙烯基三甲氧基硅烷共缩聚制得。该包覆型铂金催化剂,通过将柔性的聚己内酯二醇链段以化学键形式嵌入由正硅酸乙酯水解形成的刚性无机硅氧烷网络中,形成了兼具机械强度与韧性的互穿网络结构壳层,解决了传统包覆型催化剂易提前泄露、存储稳定性不佳的问题,该有机-无机杂化网络壳层可实现对壳层软化温度的精准调控,从而控制催化剂的释放温度,满足不同固化温度的需求。同时引入的正硅酸乙酯可以有效提高包覆型铂金催化剂与有机硅树脂的相容性。壳层构建过程中引入的乙烯基三甲氧基硅烷,使壳层表面带有乙烯基,当该催化剂应用于硅氢加成反应体系时,乙烯基可与基体中的含氢硅油发生化学反应,将包覆型铂金催化剂以化学键的形式键合于最终的交联网络中,从根本上解决了催化剂与有机硅基体因极性差异导致的相容性差和长期储存中催化剂析出的问题,显著提升了单组分体系的储存稳定性和最终产品的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878563A_ABST
    Figure CN122878563A_ABST
Patent Text Reader

Abstract

The application discloses a coated platinum gold catalyst and a preparation method and application thereof, and the coated platinum gold catalyst comprises a core material and a shell layer coated outside the core material, the core material comprises a Kast platinum gold catalyst and an inhibitor; and the shell layer is an organic-inorganic hybrid network, which is prepared by co-condensation of tetraethyl orthosilicate, polycaprolactone glycol and vinyltrimethoxysilane. The coated platinum gold catalyst has an interpenetrating network structure shell with mechanical strength and toughness, solves the problem of poor storage stability of traditional coated catalysts, and can also realize accurate control of the softening temperature of the shell layer, so as to meet the needs of different curing temperatures. Meanwhile, the compatibility of the coated platinum gold catalyst with silicone resin is high, the problems of poor compatibility and catalyst precipitation in long-term storage caused by the polarity difference between the traditional catalyst and the silicone matrix are solved, and the storage stability of a single-component system and the reliability of a final product are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, and relates to a platinum catalyst, its preparation method and application, specifically to a coated platinum catalyst, its preparation method and application. Background Technology

[0002] Addition-cure liquid silicone rubber (LSR) is widely used in electronic packaging, medical devices, automotive parts, and flexible displays due to its excellent high and low temperature resistance, electrical insulation, chemical stability, and biocompatibility. Its curing mechanism involves a hydrosilylation reaction between vinyl polysiloxane and hydrogen-containing polysiloxane under platinum catalyst catalysis, forming a three-dimensional network structure.

[0003] Among numerous platinum catalysts, Karstedt platinum catalysts are the most widely used. Specifically, Karstedt catalysts refer to complexes of platinum and tetramethyldivinyldisiloxane, possessing advantages such as high catalytic activity and fast reaction rates. However, traditional Karstedt catalysts have the following technical drawbacks: For two-component silicone rubber systems, the catalyst still exhibits some catalytic activity at room temperature, resulting in a short shelf life (typically only a few hours). To address this issue, the two components can be packaged separately. However, this method requires precise metering, mixing, and vacuum degassing of the silicone rubber before use, which is complex and prone to introducing air bubbles. Alternatively, single-component packaging can be used, extending the room temperature storage time by adding inhibitors to the silicone rubber system. However, the presence of inhibitors affects the high-temperature curing speed of the silicone system, and the inhibitory effect is difficult to precisely balance with its dosage. For highly filled silicone rubber systems (such as thermally conductive silicone and conductive silicone), small catalyst molecules are easily adsorbed or migrated by the filler, leading to uneven catalyst dispersion and subsequent localized post-curing, severely impacting the long-term reliability of the product.

[0004] To overcome the aforementioned technical shortcomings, researchers have gradually developed coated platinum catalysts in recent years, achieving single-component packaging and on-demand curing through physical isolation: the catalyst is encapsulated within the wall material, remaining inert at room temperature and releasing only when heated to the softening temperature of the wall material. Currently, coated catalysts mainly include the following categories: (1) Thermoplastic resin encapsulation type, such as the microencapsulated platinum catalyst disclosed in Chinese Patent CN104371106A, which uses polycaprolactone thermoplastic resin as the wall material and prepares microcapsules by solvent evaporation. In this type of technology, the softening temperature of the wall material is determined by the glass transition temperature or melting point of the resin, and can be controlled to a certain extent by the type and molecular weight of the resin. However, it has the following technical problems: the wall material is a pure organic polymer, which has a large difference in polarity with the organosilicon matrix (polydimethylsiloxane), resulting in poor compatibility. The microcapsules are prone to agglomeration or sedimentation in the silica gel. Moreover, it lacks chemical bonding, and cracks are easily generated at the interface between the microcapsules and the matrix during long-term storage or use, which leads to premature leakage of the catalyst and affects storage stability.

[0005] (2) Wax-coated type, such as the capsule-type platinum catalyst disclosed in Chinese patent CN118788386A, uses Fischer-Tropsch wax, polyethylene wax, silicone wax, etc. as shell materials and prepares capsules by melt emulsification. Wax materials have a low softening point and good hydrophobicity, but their mechanical strength is low and they are prone to cracking during silicone rubber compounding; moreover, there are still differences in the chemical structure between wax and organosilicon matrix, and compatibility needs to be improved.

[0006] (3) Inorganic carrier adsorption type, such as the post-curing platinum catalyst base disclosed in Chinese Patent CN119859414 A, in which the platinum catalyst is adsorbed onto the surface of an inorganic carrier such as mesoporous alumina and then mixed with silicone oil. This type of technology can effectively prevent catalyst migration, but the interface bonding between the inorganic carrier and the organosilicon matrix is ​​weak, and there is a risk of interface debonding; moreover, the carrier itself does not participate in crosslinking, which may have a negative impact on the mechanical properties and transparency of the silicone rubber; in addition, this loading method can lead to unstable polymerization, especially the release of platinum is difficult to control.

[0007] As can be seen from the above, existing coated catalysts still have shortcomings in terms of release temperature adjustability, compatibility with organosilicon matrix, and anti-precipitation stability, making it difficult to meet the requirements of high-performance single-component silicone rubber (especially high-filler filled systems) for long-term catalyst stability and curing controllability.

[0008] In view of this, it is necessary to further improve the existing coated platinum catalysts. Summary of the Invention

[0009] Therefore, the technical problem to be solved by the present invention is that the existing coated platinum catalysts have poor temperature controllability, poor storage stability, poor compatibility with organosilicon matrix, and insufficient anti-precipitation stability. Therefore, the present invention proposes a coated platinum catalyst with adjustable room temperature, high stability, good compatibility, and excellent anti-precipitation performance, as well as its preparation method and application.

[0010] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: The first aspect of this invention provides a coated platinum catalyst, comprising: a core material and a shell layer covering the outside of the core material, wherein the core material comprises a caster platinum catalyst and an inhibitor, wherein the concentration of the caster platinum catalyst is 1000-5000 ppm and the concentration of the inhibitor is 50-150 ppm; the shell layer is an organic-inorganic hybrid network, wherein the organic-inorganic hybrid network is obtained by copolymerization of tetraethyl orthosilicate, polycaprolactone diol and vinyltrimethoxysilane.

[0011] Preferably, the organic-inorganic hybrid network is prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol and vinyltrimethoxysilane in a mass ratio of 0.4:1:0.2-1:1:0.4.

[0012] Preferably, the Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane; the inhibitor is any one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, and 3,5-dimethyl-1-hexyn-3-ol.

[0013] Preferably, the number-average molecular weight of the polycaprolactone diol is 500-2000 g / mol.

[0014] A second aspect of the present invention provides a method for preparing the aforementioned coated platinum catalyst, comprising the following steps: S1. Oil Phase Preparation: Under nitrogen protection, polycaprolactone diol is dissolved in petroleum ether at a mass ratio of 0.05:1 to 0.5:1. The solution is heated to 50-60°C and stirred until dissolved. After cooling to 20-30°C, a caster platinum catalyst, an inhibitor, tetraethyl orthosilicate, and vinyltrimethoxysilane are added. The mass ratio of the caster platinum catalyst to the inhibitor is 20:1 to 50:1; the mass ratio of the caster platinum catalyst to tetraethyl orthosilicate is 1:0.2 to 1:1; and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.4:1:0.2 to 1:1:0.4. The solution is stirred until homogeneous to obtain the oil phase. S2. Aqueous phase preparation: Modified nano zinc oxide is dispersed in deionized water, wherein the mass ratio of modified nano zinc oxide to deionized water is 0.005:1-0.02:1, and the pH value is adjusted to 5-6.5 to obtain the aqueous phase. S3. Preparation of Pickering emulsion: The oil phase is added to the aqueous phase at a speed of 6000-15000 rpm and reacted for 3-10 min to form an oil-in-water Pickering emulsion, wherein the mass ratio of the oil phase to the aqueous phase is 1:5-1:20. S4. Interfacial polymerization coating: An organotin catalyst is added to the Pickering emulsion, the amount of which is 0.01-0.03% of the mass of the oil phase. The mixture is stirred at 30-45°C for 12-36 hours at a stirring speed of 200-800 rpm, so that tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase undergo a co-condensation reaction at the oil-water interface to form a preproduct of an organic-inorganic hybrid network shell coating the core material. S5. Post-processing: The preproduct is centrifuged, washed, and dried to obtain the coated platinum catalyst.

[0015] Preferably, in step S2, the modified nano-zinc oxide is prepared by the following steps: Disperse 3-8 parts by mass of nano zinc oxide in a mixed solution consisting of 80-95 parts by mass of ethanol and 5-20 parts by mass of water to obtain a premix. Add 0.3-0.8 parts by mass of vinyltrimethoxysilane to the premix and adjust the pH to 3-5. React at 60-80°C for 6-10 hours. Centrifuge, wash, and dry the product obtained from the reaction to obtain modified nano zinc oxide.

[0016] Preferably, the particle size of the nano zinc oxide is 10-100 nm.

[0017] Preferably, the organotin catalyst is at least one of dibutyltin dilaurate, stannous octoate, or dibutyltin diacetate; in step S5, the preproduct is centrifuged at 5000-10000 rpm for 10-30 min, washed 2-5 times with methanol, then washed 2-5 times with petroleum ether, and finally washed 1-2 times with octamethylcyclotetrasiloxane. After washing, it is vacuum dried at 25-40°C for 12-24 hours.

[0018] A third aspect of this invention provides the application of the aforementioned coated platinum catalyst in a single-component thermally conductive gel, wherein the single-component thermally conductive gel is prepared by the following steps: After mixing 86-90 parts by weight of thermally conductive filler, 6-9.6 parts by weight of vinyl silicone oil, 0.1-0.3 parts by weight of the coated platinum catalyst, and 0.8-1.5 parts by weight of silane coupling agent evenly, 1.2-2.4 parts by weight of side-chain hydrogen-containing silicone oil and 0.6-1.0 parts by weight of double-ended hydrogen-containing silicone oil are added, and the mixture is stirred and mixed. After vacuum degassing, a single-component thermally conductive gel is obtained.

[0019] Preferably, the thermally conductive filler is composed of a mixture of zinc oxide with a particle size of 30-50 nm, aluminum oxide with a particle size of 2-3 μm, and aluminum oxide with a particle size of 15-20 μm, wherein the mass ratio of the zinc oxide with a particle size of 30-50 nm, the aluminum oxide with a particle size of 2-3 μm, and the aluminum oxide with a particle size of 15-20 μm is 1:2:7-1:3:6; the vinyl silicone oil has a viscosity of 1000-8000 mPa·s and a vinyl content of 0.16-2.5%; the silane coupling agent is one of decyltrimethoxysilane, dodecanetrimethoxysilane, or hexadecanetrimethoxysilane; the side-chain hydrogen-containing silicone oil has a viscosity of 20-100 mPa·s and a hydrogen content of 0.1-1.2%; the double-ended hydrogen-containing silicone oil has a viscosity of 20-40 mPa·s and a hydrogen content of 0.04-0.19%.

[0020] The technical solution of the present invention has the following advantages compared with the prior art: The coated platinum catalyst provided by this invention comprises: a core material and a shell layer covering the core material. The core material includes a caster platinum catalyst and an inhibitor. In the coated platinum catalyst, the concentration of the caster platinum catalyst is 1000-5000 ppm, and the concentration of the inhibitor is 50-150 ppm. The shell layer is an organic-inorganic hybrid network, which is prepared by co-condensation of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane. This coated platinum catalyst, by embedding flexible polycaprolactone diol segments into a rigid inorganic siloxane network formed by the hydrolysis of tetraethyl orthosilicate through chemical bonds, forms an interpenetrating network structure shell layer with both mechanical strength and toughness. This solves the problems of premature leakage and poor storage stability of traditional coated catalysts. This organic-inorganic hybrid network shell layer allows for precise control of the shell layer softening temperature, thereby controlling the catalyst release temperature and meeting the requirements of different curing temperatures. The introduction of tetraethyl orthosilicate effectively improves the compatibility between the coated platinum catalyst and the organosilicon resin. The vinyltrimethoxysilane introduced during shell construction imbues the shell surface with vinyl groups. When this catalyst is applied to a hydrosilylation reaction system, the vinyl groups can chemically react with the hydrogen-containing silicone oil in the matrix, bonding the coated platinum catalyst to the final cross-linked network through chemical bonds. This fundamentally solves the problems of poor compatibility between the catalyst and the organosilicon matrix due to polarity differences, as well as catalyst precipitation during long-term storage, significantly improving the storage stability of the single-component system and the reliability of the final product. Attached Figure Description

[0021] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein... Figure 1This is the FT-IR test pattern of the coated platinum catalyst provided in Example 1 of the present invention; Figure 2 This is a SEM image of the coated platinum catalyst provided in Example 1 of the present invention; Figure 3 This is the XRD pattern of the coated platinum catalyst provided in Example 1 of the present invention; Figure 4 This is a DSC curve of the coated platinum catalyst provided in Example 1 of the present invention. Detailed Implementation

[0022] Example 1 This embodiment provides a coated platinum catalyst, which is a core-shell structured microsphere comprising a core material and a shell coating the core material. The core material includes a Castrol platinum catalyst and an inhibitor. The Castrol platinum catalyst content is 3000 ppm, and the inhibitor content is 90 ppm. The shell is an organic-inorganic hybrid network prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

[0023] An organic-inorganic hybrid network shell, prepared by the copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane, can encapsulate a core material containing a Castiglione platinum catalyst and an inhibitor. The core material, composed of specific amounts, ensures sufficient catalytic activity to meet the requirements of subsequent rapid curing. The inhibitor prevents the Castiglione platinum catalyst from initiating polymerization at room temperature. Its content ensures the long-term stability of the encapsulated platinum catalyst at room temperature without significantly slowing down the reaction rate during subsequent heat curing due to excessive inhibition.

[0024] In the shell material, tetraethyl orthosilicate (TEOS) and polycaprolactone diol (PCL) undergo an transesterification reaction. The flexible PCL molecular chains are chemically bonded into the rigid silica network formed by the hydrolysis of TEOS, thus forming an interpenetrating network structure. Compared with traditional pure organic or pure inorganic shells, this material combines mechanical strength and flexibility. The organic-inorganic hybrid shell formed by combining low-melting-point PCL with SiO2 generated from the hydrolysis of TEOS can also effectively adjust the release temperature of the platinum catalyst. The synergy of the two can achieve wide-temperature-range, high-precision control of the platinum catalyst release, thereby enabling on-demand curing at different temperatures. This is superior to the adjustment capability of existing single-material shells. The introduction of TEOS can effectively improve the compatibility between the capsule and the silicone resin, solving the technical problems of easy breakage of traditional organic shells and high brittleness and poor compatibility of inorganic shells. Meanwhile, vinyltrimethoxysilane, as a precursor, participates in the shell construction and introduces reactive vinyl groups. When the silicone rubber is cured, the vinyl groups on the shell surface undergo hydrosilylation with Si-H, chemically bonding the microspheres into the cross-linked network. This solves the problems of poor compatibility caused by physical blending and the precipitation of platinum catalyst during long-term storage, thereby improving the long-term stability and product reliability of the single-component high-filled silicone rubber system.

[0025] Specifically, in this embodiment, the mass ratio of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane is 0.6:1:0.2, and the number-average molecular weight of polycaprolactone diol is 830 g / mol. The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane. In this embodiment, the Castel platinum catalyst can be any one of Dow Corning DC4000, Heraeus PT5000, Guangzhou Silicon Friends New Material Technology Co., Ltd. PT-5000, Jiangxi Betterley New Material Co., Ltd. PT-3000, or Shanghai Neutron Star Chemical Technology Co., Ltd. PC-46. The inhibitor is 1-ethynyl-1-cyclohexanol.

[0026] This embodiment also provides a method for preparing the above-mentioned coated platinum catalyst, comprising the following steps: S1. Oil Phase Preparation: In a three-necked flask equipped with a stirrer, condenser, and glass stopper, petroleum ether and polycaprolactone diol are added. Nitrogen gas is introduced while stirring, allowing polycaprolactone diol to dissolve in petroleum ether under nitrogen protection. The mixture is then heated to 60°C and stirred until the polycaprolactone diol is completely dissolved. The temperature is then lowered to 20°C, and Castrol platinum catalyst, 1-ethynyl-1-cyclohexanol, tetraethyl orthosilicate, and vinyltrimethoxysilane are slowly added dropwise to the resulting cooled mixture. After the addition is complete, the mixture is stirred until homogeneous to obtain the oil phase. In this embodiment, the mass ratio of polycaprolactone diol to petroleum ether is 0.2:1, the mass ratio of Castrol platinum catalyst to 1-ethynyl-1-cyclohexanol is 30:1, the mass ratio of Castrol platinum catalyst to tetraethyl orthosilicate is 1:0.6, and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.6:1:0.2.

[0027] S2. Preparation of the aqueous phase: Disperse the modified nano zinc oxide in deionized water and stir ultrasonically until a homogeneous solution is formed. The mass ratio of modified nano zinc oxide to deionized water is 0.01:1. Adjust the pH of the solution system to 5.5 with dilute hydrochloric acid to obtain the aqueous phase. Then transfer the aqueous phase to a three-necked flask equipped with a condenser, a stirrer and a glass stopper, and continue stirring.

[0028] In this embodiment, the modified nano-zinc oxide was prepared by the following method: 6 parts by mass of nano-zinc oxide with an average particle size of 20 nm were added to a beaker containing a mixed solution of 90 parts by mass of ethanol and 10 parts by mass of water, and ultrasonically dispersed for 10 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer, and a glass stopper. Under continuous stirring, 0.4 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 4 with hydrochloric acid, and the temperature was raised to 75°C. The reaction was carried out at this temperature for 8 h. After the reaction, the temperature was lowered to room temperature, centrifuged, and the obtained product was washed three times with ethanol and dried at 60°C to obtain vinyltrimethoxysilane-modified nano-zinc oxide. In modified nano zinc oxide, vinyltrimethoxysilane is used to control the hydrophilic / hydrophobic balance of the zinc oxide surface (contact angle between 30-80°), making it an ideal pickering emulsifier. By using this modified nano zinc oxide instead of traditional silica as the pickering emulsifier, the high thermal conductivity of zinc oxide can be utilized to solve the problem of decreased thermal conductivity caused by the introduction of traditional silica capsules.

[0029] S3. Preparation of Pickering emulsion: The oil phase prepared above is slowly added dropwise to the aqueous phase at a speed of 8000 rpm. The mixture gradually turns milky white. After the addition is complete, the mixture is stirred for 8 minutes to form a stable oil-in-water Pickering emulsion. The mass ratio of the oil phase to the aqueous phase is 1:8.

[0030] S4. Interfacial polymerization coating: Dibutyltin dilaurate catalyst is slowly added dropwise to the Pickering emulsion. The amount of dibutyltin dilaurate catalyst added is 0.02% of the oil phase mass. The resulting solution system is heated to 40°C and reacted continuously at a stirring speed of 600 rpm for 24 hours. This allows tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase to undergo a co-condensation reaction at the oil-water interface, forming a microsphere preproduct with an organic-inorganic hybrid network shell coating the core material.

[0031] S5. Post-treatment: The preproduct was centrifuged at 8000 rpm for 15 min. The centrifuged product was washed three times with methanol, then three times with petroleum ether, and finally twice with octamethylcyclotetrasiloxane to clean the platinum catalyst on the surface of the microspheres. The washed product was then vacuum dried at 30°C for 16 h to obtain the coated platinum catalyst.

[0032] This embodiment also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, which is prepared by the following steps: 88 parts by weight of thermally conductive filler, 8.0 parts by weight of vinyl silicone oil (viscosity 6300 mPa·s, vinyl content 0.96%), 0.12 parts by weight of the above-mentioned coated platinum catalyst, and 1.0 parts by weight of hexadecanetrimethoxysilane were mixed evenly. Then, 1.6 parts by weight of side-chain hydrogen-containing silicone oil (viscosity 90 mPa·s, hydrogen content 0.28%) and 0.9 parts by weight of double-ended hydrogen-containing silicone oil (viscosity 30 mPa·s, hydrogen content 0.1%) were added and the mixture was stirred and mixed. After vacuum degassing, a single-component thermally conductive gel was obtained. In this embodiment, the thermally conductive filler is composed of zinc oxide with an average particle size of 40 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm, wherein the mass ratio of zinc oxide with an average particle size of 40 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm is 1:2:7.

[0033] In this application, the coated platinum catalyst is premixed with all reaction components and a high proportion of thermally conductive filler. Because the catalyst is isolated by the shell and cannot contact the reactants at room temperature, the system remains in a single-component liquid state with a long pot life. When curing is required, heating softens / melts the shell, releasing the core catalyst and rapidly initiating a hydrosilylation reaction, causing the entire system to crosslink and solidify. The vinyl groups on the shell surface also participate in the reaction, chemically bonding the microspheres into a three-dimensional network, solving the problems of poor compatibility and precipitation after long-term use caused by physical blending. The thermally conductive filler uses a multi-level blend of nano-zinc oxide and micron-sized alumina to construct efficient thermal conduction pathways. A silane coupling agent is used to improve the interfacial bonding between the filler and the organosilicon matrix.

[0034] Example 2 This embodiment provides a coated platinum catalyst, which is a core-shell structured microsphere comprising a core material and a shell coating the core material. The core material includes a Castrol platinum catalyst and an inhibitor. The Castrol platinum catalyst content is 5000 ppm, and the inhibitor content is 150 ppm. The shell is an organic-inorganic hybrid network prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

[0035] Specifically, in this embodiment, the mass ratio of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane is 1:1:0.4, and the number-average molecular weight of polycaprolactone diol is 1250 g / mol. The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane, and the inhibitor is 2-methyl-3-butyn-2-ol.

[0036] This embodiment also provides a method for preparing the above-mentioned coated platinum catalyst, comprising the following steps: S1. Oil phase preparation: In a three-necked flask equipped with a stirrer, condenser, and glass stopper, petroleum ether and polycaprolactone diol are added. Nitrogen gas is introduced while stirring, allowing polycaprolactone diol to dissolve in petroleum ether under nitrogen protection. The mixture is then heated to 55°C and stirred until the polycaprolactone diol is completely dissolved. The temperature is then lowered to 25°C, and Castrol platinum catalyst, 2-methyl-3-butyn-2-ol, tetraethyl orthosilicate, and vinyltrimethoxysilane are slowly added dropwise to the resulting cooled mixture. After the addition is complete, the mixture is stirred until homogeneous to obtain the oil phase. In this embodiment, the mass ratio of polycaprolactone diol to petroleum ether is 0.05:1, the mass ratio of Castrol platinum catalyst to 2-methyl-3-butyn-2-ol is 20:1, the mass ratio of Castrol platinum catalyst to tetraethyl orthosilicate is 1:0.2, and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 1:1:0.4.

[0037] S2. Preparation of the aqueous phase: Disperse the modified nano zinc oxide in deionized water and stir ultrasonically until a homogeneous solution is formed. The mass ratio of modified nano zinc oxide to deionized water is 0.02:1. Adjust the pH of the solution system to 6.5 with dilute hydrochloric acid to obtain the aqueous phase. Then transfer the aqueous phase to a three-necked flask equipped with a condenser, a stirrer and a glass stopper, and continue stirring.

[0038] In this embodiment, the modified nano zinc oxide was prepared by the following method: 8 parts by mass of nano zinc oxide with an average particle size of 10 nm were added to a beaker containing a mixed solution of 95 parts by mass of ethanol and 5 parts by mass of water, and ultrasonically dispersed for 5 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer and a glass stopper. Under continuous stirring, 0.8 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 3 with acetic acid and the temperature was raised to 60 °C. The reaction was carried out at this temperature for 10 h. After the reaction, the temperature was lowered to room temperature and centrifuged. The obtained product was washed three times with ethanol and dried at 70 °C to obtain vinyltrimethoxysilane modified nano zinc oxide.

[0039] S3. Preparation of Pickering emulsion: The oil phase prepared above is slowly added dropwise to the aqueous phase at a speed of 6000 rpm. The mixture gradually turns milky white. After the addition is complete, the mixture is stirred for 10 minutes to form a stable oil-in-water Pickering emulsion. The mass ratio of the oil phase to the aqueous phase is 1:5.

[0040] S4. Interfacial polymerization coating: Stannous octoate catalyst is slowly added dropwise to the Pickering emulsion. The amount of stannous octoate catalyst added is 0.03% of the oil phase mass. The resulting solution system is heated to 30°C and reacted continuously at a stirring speed of 200 rpm for 36 h. This allows tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase to undergo a co-condensation reaction at the oil-water interface, forming a microsphere preproduct with an organic-inorganic hybrid network shell coating the core material.

[0041] S5. Post-treatment: The preproduct was centrifuged at 10,000 rpm for 10 min. The centrifuged product was washed 5 times with methanol, then 5 times with petroleum ether, and finally once with octamethylcyclotetrasiloxane to clean the platinum catalyst on the surface of the microspheres. The washed product was then vacuum dried at 25°C for 24 h to obtain the coated platinum catalyst.

[0042] This embodiment also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, which is prepared by the following steps: 86 parts by weight of thermally conductive filler, 6.0 parts by weight of vinyl silicone oil (viscosity 1000 mPa·s, vinyl content 2.5%), 0.3 parts by weight of the above-mentioned coated platinum catalyst, and 1.5 parts by weight of decyltrimethoxysilane were mixed evenly. Then, 1.2 parts by weight of side-chain hydrogen-containing silicone oil (viscosity 20 mPa·s, hydrogen content 1.2%) and 0.6 parts by weight of double-ended hydrogen-containing silicone oil (viscosity 20 mPa·s, hydrogen content 0.19%) were added and the mixture was stirred and mixed. After vacuum degassing, a single-component thermally conductive gel was obtained. In this embodiment, the thermally conductive filler is composed of zinc oxide with an average particle size of 50 nm, aluminum oxide with an average particle size of 3 μm, and aluminum oxide with an average particle size of 15 μm, wherein the mass ratio of zinc oxide with an average particle size of 50 nm, aluminum oxide with an average particle size of 3 μm, and aluminum oxide with an average particle size of 15 μm is 1:2.5:6.5.

[0043] Example 3 This embodiment provides a coated platinum catalyst, which is a core-shell structured microsphere comprising a core material and a shell layer covering the core material. The core material includes a Castrol platinum catalyst and an inhibitor. The Castrol platinum catalyst content is 1000 ppm, and the inhibitor content is 50 ppm. The shell layer is an organic-inorganic hybrid network, which is prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

[0044] Specifically, in this embodiment, the mass ratio of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane is 0.4:1:0.2, and the number average molecular weight of polycaprolactone diol is 500 g / mol. The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane, and the inhibitor is 3,5-dimethyl-1-hexyn-3-ol.

[0045] This embodiment also provides a method for preparing the above-mentioned coated platinum catalyst, comprising the following steps: S1. Oil phase preparation: In a three-necked flask equipped with a stirrer, condenser, and glass stopper, add petroleum ether and polycaprolactone diol. While stirring, purge with nitrogen gas to dissolve the polycaprolactone diol in the petroleum ether under nitrogen protection. Then, heat the mixture to 50°C and stir until the polycaprolactone diol is completely dissolved. Reduce the temperature to 20°C and slowly add Castrol platinum catalyst and 3,5-dimethyl-1-hexyn-3-ol to the resulting cooled mixture. After the addition of tetraethyl orthosilicate and vinyltrimethoxysilane is completed, the mixture is stirred evenly to obtain the oil phase. In this embodiment, the mass ratio of polycaprolactone diol to petroleum ether is 0.5:1, the mass ratio of caster platinum catalyst to 3,5-dimethyl-1-hexyn-3-ol is 50:1, the mass ratio of caster platinum catalyst to tetraethyl orthosilicate is 1:1, and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.4:1:0.2.

[0046] S2. Preparation of the aqueous phase: Disperse the modified nano zinc oxide in deionized water and stir ultrasonically until a homogeneous solution is formed. The mass ratio of modified nano zinc oxide to deionized water is 0.005:1. Adjust the pH of the solution system to 5.0 with dilute hydrochloric acid to obtain the aqueous phase. Then transfer the aqueous phase to a three-necked flask equipped with a condenser, a stirrer and a glass stopper, and continue stirring.

[0047] In this embodiment, the modified nano-zinc oxide was prepared by the following method: 3 parts by mass of nano-zinc oxide with an average particle size of 100 nm were added to a beaker containing a mixed solution of 80 parts by mass of ethanol and 20 parts by mass of water, and ultrasonically dispersed for 8 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer, and a glass stopper. Under continuous stirring, 0.3 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 5 with nitric acid, and the temperature was raised to 80°C. The reaction was carried out at this temperature for 6 h. After the reaction, the temperature was lowered to room temperature, centrifuged, and the obtained product was washed three times with ethanol and dried at 70°C to obtain vinyltrimethoxysilane-modified nano-zinc oxide.

[0048] S3. Preparation of Pickering emulsion: The oil phase prepared above is slowly added dropwise to the aqueous phase at a speed of 15000 rpm. The mixture gradually turns milky white. After the addition is complete, the mixture is stirred for 3 minutes to form a stable oil-in-water Pickering emulsion. The mass ratio of the oil phase to the aqueous phase is 1:20.

[0049] S4. Interfacial polymerization coating: Dibutyltin diacetate catalyst is slowly added dropwise to the Pickering emulsion. The amount of dibutyltin diacetate catalyst added is 0.01% of the oil phase mass. The resulting solution system is heated to 45°C and reacted continuously at a stirring speed of 800 rpm for 12 hours. This allows tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase to undergo a co-condensation reaction at the oil-water interface, forming a microsphere preproduct with an organic-inorganic hybrid network shell coating the core material.

[0050] S5. Post-treatment: The preproduct was centrifuged at 5000 rpm for 30 min. The centrifuged product was washed twice with methanol, then twice with petroleum ether, and finally twice with octamethylcyclotetrasiloxane to clean the platinum catalyst on the surface of the microspheres. The washed product was then vacuum dried at 40 °C for 12 h to obtain the coated platinum catalyst.

[0051] This embodiment also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, which is prepared by the following steps: 90 parts by weight of thermally conductive filler, 9.6 parts by weight of vinyl silicone oil (viscosity 8000 mPa·s, vinyl content 0.16%), 0.1 parts by weight of the above-mentioned coated platinum catalyst, and 0.8 parts by weight of hexadecanetrimethoxysilane were mixed evenly. Then, 2.4 parts by weight of side-chain hydrogen-containing silicone oil (viscosity 20 mPa·s, hydrogen content 0.1%) and 0.8 parts by weight of double-ended hydrogen-containing silicone oil (viscosity 40 mPa·s, hydrogen content 0.04%) were added and the mixture was stirred and mixed. After vacuum degassing, a single-component thermally conductive gel was obtained. In this embodiment, the thermally conductive filler is composed of zinc oxide with an average particle size of 30 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm, wherein the mass ratio of zinc oxide with an average particle size of 30 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm is 1:3:6.

[0052] Example 4 This embodiment provides a coated platinum catalyst, which is a core-shell structured microsphere comprising a core material and a shell coating the core material. The core material includes a Castrol platinum catalyst and an inhibitor. The Castrol platinum catalyst content is 2500 ppm, and the inhibitor content is 80 ppm. The shell is an organic-inorganic hybrid network prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

[0053] Specifically, in this embodiment, the mass ratio of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane is 0.6:1:0.3, and the number average molecular weight of polycaprolactone diol is 2000 g / mol. The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane, and the inhibitor is 1-ethynyl-1-cyclohexanol.

[0054] This embodiment also provides a method for preparing the above-mentioned coated platinum catalyst, comprising the following steps: S1. Oil phase preparation: In a three-necked flask equipped with a stirrer, condenser, and glass stopper, petroleum ether and polycaprolactone diol are added. Nitrogen gas is introduced while stirring, allowing polycaprolactone diol to dissolve in petroleum ether under nitrogen protection. The mixture is then heated to 60°C and stirred until the polycaprolactone diol is completely dissolved. The temperature is then lowered to 20°C, and Castrol platinum catalyst, 1-ethynyl-1-cyclohexanol, tetraethyl orthosilicate, and vinyltrimethoxysilane are slowly added dropwise to the resulting cooled mixture. After the addition is complete, the mixture is stirred until homogeneous to obtain the oil phase. In this embodiment, the mass ratio of polycaprolactone diol to petroleum ether is 0.25:1, the mass ratio of Castrol platinum catalyst to 1-ethynyl-1-cyclohexanol is 35:1, the mass ratio of Castrol platinum catalyst to tetraethyl orthosilicate is 1:0.4, and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.6:1:0.3.

[0055] S2. Preparation of the aqueous phase: Disperse the modified nano zinc oxide in deionized water and stir ultrasonically until a homogeneous solution is formed. The mass ratio of modified nano zinc oxide to deionized water is 0.01:1. Adjust the pH of the solution system to 5.5 with dilute hydrochloric acid to obtain the aqueous phase. Then transfer the aqueous phase to a three-necked flask equipped with a condenser, a stirrer and a glass stopper, and continue stirring.

[0056] In this embodiment, the modified nano-zinc oxide was prepared by the following method: 5 parts by mass of nano-zinc oxide with an average particle size of 46 nm were added to a beaker containing a mixed solution of 90 parts by mass of ethanol and 10 parts by mass of water, and ultrasonically dispersed for 9 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer and a glass stopper. Under continuous stirring, 0.5 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 4.5 with sulfuric acid and the temperature was raised to 70 °C. The reaction was carried out at this temperature for 9 h. After the reaction, the temperature was lowered to room temperature and centrifuged. The obtained product was washed three times with ethanol and dried at 80 °C to obtain vinyltrimethoxysilane modified nano-zinc oxide.

[0057] S3. Preparation of Pickering emulsion: The oil phase prepared above is slowly added dropwise to the aqueous phase at a speed of 12000 rpm. The mixture gradually turns milky white. After the addition is complete, the mixture is stirred for 7 minutes to form a stable oil-in-water Pickering emulsion. The mass ratio of the oil phase to the aqueous phase is 1:9.

[0058] S4. Interfacial polymerization coating: Stannous octoate catalyst is slowly added dropwise to the Pickering emulsion. The amount of stannous octoate catalyst added is 0.02% of the oil phase mass. The resulting solution system is heated to 45°C and reacted continuously at a stirring speed of 500 rpm for 32 hours. This allows tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase to undergo a co-condensation reaction at the oil-water interface, forming a microsphere preproduct with an organic-inorganic hybrid network shell coating the core material.

[0059] S5. Post-treatment: The preproduct was centrifuged at 8000 rpm for 18 min. The centrifuged product was washed twice with methanol, then three times with petroleum ether, and finally twice with octamethylcyclotetrasiloxane to clean the platinum catalyst on the surface of the microspheres. The washed product was then vacuum dried at 30°C for 24 h to obtain the coated platinum catalyst.

[0060] This embodiment also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, which is prepared by the following steps: 88 parts by weight of thermally conductive filler, 7.2 parts by weight of vinyl silicone oil (viscosity 2000 mPa·s, vinyl content 1.3%), 0.2 parts by weight of the above-mentioned coated platinum catalyst, and 1.2 parts by weight of dodecanetrimethoxysilane were mixed evenly. Then, 1.5 parts by weight of side-chain hydrogen-containing silicone oil (viscosity 80 mPa·s, hydrogen content 0.65%) and 1.0 parts by weight of double-ended hydrogen-containing silicone oil (viscosity 32 mPa·s, hydrogen content 0.07%) were added and the mixture was stirred and mixed. After vacuum degassing, a single-component thermally conductive gel was obtained. In this embodiment, the thermally conductive filler is composed of zinc oxide with an average particle size of 38 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm, wherein the mass ratio of zinc oxide with an average particle size of 38 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 20 μm is 1:2:7.

[0061] Example 5 This embodiment provides a coated platinum catalyst, which is a core-shell structured microsphere comprising a core material and a shell coating the core material. The core material includes a Castrol platinum catalyst and an inhibitor. The Castrol platinum catalyst content is 4000 ppm, and the inhibitor content is 120 ppm. The shell is an organic-inorganic hybrid network prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

[0062] Specifically, in this embodiment, the mass ratio of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane is 0.8:1:0.4, and the number-average molecular weight of polycaprolactone diol is 900 g / mol. The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane, and the inhibitor is 2-methyl-3-butyn-2-ol.

[0063] This embodiment also provides a method for preparing the above-mentioned coated platinum catalyst, comprising the following steps: S1. Oil phase preparation: In a three-necked flask equipped with a stirrer, condenser, and glass stopper, petroleum ether and polycaprolactone diol are added. Nitrogen gas is introduced while stirring, allowing polycaprolactone diol to dissolve in petroleum ether under nitrogen protection. The mixture is then heated to 60°C and stirred until the polycaprolactone diol is completely dissolved. The temperature is then lowered to 30°C, and Castrol platinum catalyst, 2-methyl-3-butyn-2-ol, tetraethyl orthosilicate, and vinyltrimethoxysilane are slowly added dropwise to the resulting cooled mixture. After the addition is complete, the mixture is stirred until homogeneous to obtain the oil phase. In this embodiment, the mass ratio of polycaprolactone diol to petroleum ether is 0.3:1, the mass ratio of Castrol platinum catalyst to 2-methyl-3-butyn-2-ol is 25:1, the mass ratio of Castrol platinum catalyst to tetraethyl orthosilicate is 1:0.5, and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.8:1:0.4.

[0064] S2. Preparation of the aqueous phase: Disperse the modified nano zinc oxide in deionized water and stir ultrasonically until a homogeneous solution is formed. The mass ratio of modified nano zinc oxide to deionized water is 0.012:1. Adjust the pH of the solution system to 5 with dilute hydrochloric acid to obtain the aqueous phase. Then transfer the aqueous phase to a three-necked flask equipped with a condenser, a stirrer and a glass stopper, and continue stirring.

[0065] In this embodiment, the modified nano zinc oxide was prepared by the following method: 5 parts by mass of nano zinc oxide with an average particle size of 20 nm were added to a beaker containing a mixed solution of 85 parts by mass of ethanol and 15 parts by mass of water, and ultrasonically dispersed for 10 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer and a glass stopper. Under continuous stirring, 0.4 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 4 with hydrochloric acid and the temperature was raised to 70 °C. The reaction was carried out at this temperature for 8 h. After the reaction, the temperature was lowered to room temperature and centrifuged. The obtained product was washed three times with ethanol and dried at 70 °C to obtain vinyltrimethoxysilane modified nano zinc oxide.

[0066] S3. Preparation of Pickering emulsion: The oil phase prepared above is slowly added dropwise to the aqueous phase at a speed of 8000 rpm. The mixture gradually turns milky white. After the addition is complete, the mixture is stirred for 6 minutes to form a stable oil-in-water Pickering emulsion. The mass ratio of the oil phase to the aqueous phase is 1:15.

[0067] S4. Interfacial polymerization coating: Dibutyltin dilaurate catalyst is slowly added dropwise to the Pickering emulsion. The amount of dibutyltin dilaurate catalyst added is 0.02% of the oil phase mass. The resulting solution system is heated to 40°C and reacted continuously at a stirring speed of 400 rpm for 28 hours. This allows tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase to undergo a co-condensation reaction at the oil-water interface, forming a microsphere preproduct with an organic-inorganic hybrid network shell coating the core material.

[0068] S5. Post-treatment: The preproduct was centrifuged at 5000 rpm for 18 min. The centrifuged product was washed three times with methanol, then three times with petroleum ether, and finally once with octamethylcyclotetrasiloxane to clean the platinum catalyst on the surface of the microspheres. The washed product was then vacuum dried at 40 °C for 24 h to obtain the coated platinum catalyst.

[0069] This embodiment also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, which is prepared by the following steps: 87 parts by weight of thermally conductive filler, 8.5 parts by weight of vinyl silicone oil (viscosity 5000 mPa·s, vinyl content 2.2%), 0.1 parts by weight of the above-mentioned coated platinum catalyst, and 1.2 parts by weight of hexadecanetrimethoxysilane were mixed evenly. Then, 2.1 parts by weight of side-chain hydrogen-containing silicone oil (viscosity 60 mPa·s, hydrogen content 0.9%) and 0.6 parts by weight of double-ended hydrogen-containing silicone oil (viscosity 28 mPa·s, hydrogen content 0.12%) were added and the mixture was stirred and mixed. After vacuum degassing, a single-component thermally conductive gel was obtained. In this embodiment, the thermally conductive filler is composed of zinc oxide with an average particle size of 30 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 15 μm, wherein the mass ratio of zinc oxide with an average particle size of 30 nm, aluminum oxide with an average particle size of 2 μm, and aluminum oxide with an average particle size of 15 μm is 1:3:6.

[0070] Comparative Example 1 This comparative example provides a coated platinum catalyst, the preparation method of which is basically the same as that of Example 1. The difference is that in step S2, modified nano zinc oxide is not used, but zinc oxide is used. The other steps and reaction parameters are the same as those of Example 1.

[0071] This comparative example also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, and the preparation method of the thermally conductive gel is the same as that in Example 1.

[0072] Comparative Example 2 This comparative example provides a coated platinum catalyst, the preparation method of which is basically the same as that of Example 1, except that modified nano zinc oxide is not used in step S2, but modified silica is used instead. Specifically, the modified silica is prepared by the following method: Six parts by mass of nano-silica with an average particle size of 20 nm were added to a beaker containing a mixed solution of 90 parts by mass of ethanol and 10 parts by mass of water. The mixture was ultrasonically dispersed for 10 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer, and a glass stopper. Under continuous stirring, 0.4 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 4 with hydrochloric acid, and the temperature was raised to 75 °C. The reaction was carried out at this temperature for 8 h. After the reaction, the mixture was cooled to room temperature, centrifuged, and the obtained product was washed three times with ethanol and dried at 60 °C to obtain vinyltrimethoxysilane-modified nano-silica.

[0073] The other steps and reaction parameters are the same as in Example 1.

[0074] This comparative example also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, and the preparation method of the thermally conductive gel is the same as that in Example 1.

[0075] Comparative Example 3 This comparative example provides a coated platinum catalyst, the preparation method of which is basically the same as that of Example 1, except that the preparation method of modified nano-zinc oxide in step S2 is different. Specifically, the modified nano-zinc oxide in this comparative example is prepared by the following method: Six parts by mass of zinc oxide nanoparticles with an average particle size of 20 nm were added to a beaker containing a mixed solution of 90 parts by mass of ethanol and 10 parts by mass of water. The mixture was ultrasonically dispersed for 10 min to obtain a premix. The premix was transferred to a three-necked flask equipped with a condenser, a stirrer, and a glass stopper. Under continuous stirring, 1.2 parts by mass of vinyltrimethoxysilane were added dropwise. The pH of the solution was adjusted to 4 with hydrochloric acid, and the temperature was raised to 75 °C. The reaction was carried out at this temperature for 8 h. After the reaction, the mixture was cooled to room temperature, centrifuged, and the obtained product was washed three times with ethanol and dried at 60 °C to obtain vinyltrimethoxysilane-modified zinc oxide nanoparticles.

[0076] The other steps and reaction parameters are the same as in Example 1.

[0077] This comparative example also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, and the preparation method of the thermally conductive gel is the same as that in Example 1.

[0078] Comparative Example 4 This comparative example provides a coated platinum catalyst, the preparation method of which is basically the same as that of Example 1, except that tetraethyl orthosilicate is not added in step S1. Specifically, in this comparative example, step S1 is as follows: oil phase preparation: petroleum ether and polycaprolactone diol are added to a three-necked flask equipped with a stirrer, condenser and glass stopper, and nitrogen gas is introduced while stirring, so that polycaprolactone diol dissolves in petroleum ether under nitrogen protection. Then the mixture is heated to 60°C and stirred until the polycaprolactone diol dissolves in the petroleum ether. After the alcohol is completely dissolved, the temperature is lowered to 30°C. Castel platinum catalyst, 1-ethynyl-1-cyclohexanol, and vinyltrimethoxysilane are slowly added dropwise to the resulting cooled mixed solution. After the addition is complete, the mixture is stirred until homogeneous to obtain the oil phase. In this comparative example, the mass ratio of polycaprolactone diol to petroleum ether is 0.2:1, the mass ratio of castel platinum catalyst to 1-ethynyl-1-cyclohexanol is 30:1, and the mass ratio of polycaprolactone diol to vinyltrimethoxysilane is 0.6:0.2.

[0079] The other steps and reaction parameters are the same as in Example 1.

[0080] This comparative example also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, and the preparation method of the thermally conductive gel is the same as that in Example 1.

[0081] Comparative Example 5 This comparative example provides a coated platinum catalyst, the preparation method of which is basically the same as that of Example 1, except that vinyltrimethoxysilane is not added in step S1. Specifically, in this comparative example, step S1 is as follows: oil phase preparation: petroleum ether and polycaprolactone diol are added to a three-necked flask equipped with a stirrer, condenser and glass stopper. Nitrogen gas is introduced while stirring, so that polycaprolactone diol dissolves in petroleum ether under nitrogen protection. Then the mixture is heated to 60°C and stirred until the polycaprolactone diol is completely dissolved. The temperature was lowered to 30°C, and Castel platinum catalyst, 1-ethynyl-1-cyclohexanol, and tetraethyl orthosilicate were slowly added dropwise to the resulting cooled mixed solution. After the addition was complete, the mixture was stirred until homogeneous to obtain the oil phase. In this comparative example, the mass ratio of polycaprolactone diol to petroleum ether was 0.2:1, the mass ratio of Castel platinum catalyst to 1-ethynyl-1-cyclohexanol was 30:1, the mass ratio of Castel platinum catalyst to tetraethyl orthosilicate was 1:0.6, and the mass ratio of polycaprolactone diol to tetraethyl orthosilicate was 0.6:1.

[0082] The other steps and reaction parameters are the same as in Example 1.

[0083] This comparative example also provides an application of the above-mentioned coated platinum catalyst in a single-component thermally conductive gel, and the preparation method of the thermally conductive gel is the same as that in Example 1.

[0084] Experimental Example Experimental Example 1. Fourier Transmission Infrared Spectroscopy (FT-IR) Test The infrared spectrum of the coated platinum catalyst provided in Example 1 was tested under attenuated total reflectance (ATR) mode, with a scan range of 450-4000 cm⁻¹. -1 The resolution is 4 cm. -1 The number of scans was 32. The chemical structure of the coated platinum catalyst was tested using an FT-IR spectrometer (FT-IR Tracer 100) manufactured by Shimadzu Instrument Co., LTD, Japan.

[0085] Test results are as follows Figure 1 As shown in the figure. It can be seen from the figure that in the range of 3300-3500cm... -1 A characteristic absorption peak attributable to hydroxyl groups appeared, mainly originating from polycaprolactone diol, in the range of 2700-2950 cm⁻¹. -1 Characteristic absorption peaks belonging to -CH3 and -CH2- appeared, mainly due to polycaprolactone diol and tetraethyl orthosilicate, at 1720 cm⁻¹. -1 The absorption peak, mainly caused by the C=O in polycaprolactone diol, is located at 1000-1100 cm⁻¹. -1The absorption peaks mainly originate from the Si-OC of tetraethyl orthosilicate and vinyltrimethoxysilane, at 500 cm⁻¹. -1 The absorption peak is mainly due to zinc oxide. Because polycaprolactone diol, tetraethyl orthosilicate, and vinyltrimethoxysilane undergo condensation, the absorption peak of the hydroxyl group is relatively weak, indicating that some hydroxyl groups participated in the condensation reaction. This is also evident in the infrared spectrum at 1620 cm⁻¹. -1 A slight absorption peak appeared on the left and right sides, which was caused by the introduction of the C=C double bond. The infrared spectrum indicates that a complex with vinyl groups was obtained.

[0086] 2. Scanning Electron Microscopy (SEM) Testing Scanning electron microscope (SEM) images of the coated platinum catalyst provided in Example 1: The surface morphology of the film was observed using an SEM (FEI Verios G4UC) manufactured by Thermo Fisher Scientific, USA, at an accelerating voltage of 5.0 kV. The sample surface needs to be sputtered with gold before testing.

[0087] Test results are as follows Figure 2 As shown in the figure, the coated platinum catalyst consists of uniformly shaped microspheres with a particle size of approximately 3-8 μm. The system also contains some unbound zinc oxide. It can be seen that the microspheres do not exhibit obvious cracks or defects, indicating that the coated platinum catalyst has good coating properties, preventing platinum precipitation during storage or use.

[0088] 3. X-ray diffraction (XRD) test The XRD patterns of the coated platinum catalyst provided in Example 1 were tested: The structures of zinc oxide powder before and after modification were characterized using XRD (Bruker D8, Germany). The powder was ground finely in a mortar and pestle, placed on the sample stage, and the test surface was kept flat. The scanning range of the test was 5°-85°.

[0089] Test results are as follows Figure 3As shown in the figure, multiple diffraction peaks appear in the XRD pattern, including 2θ=31.86° (100) crystal plane, 2θ=34.50° (002) crystal plane, 2θ=36.36° (101) crystal plane, 2θ=47.64° (102) crystal plane, 2θ=56.71° (110) crystal plane, 2θ=62.98° (103) crystal plane, and 2θ=68.04° (112) crystal plane. The positions of the diffraction peaks are basically consistent with those of pure hexagonal ZnO, so it can be determined that it is pure hexagonal ZnO. In addition, other characteristic diffraction peaks appeared in the XRD pattern, such as 2θ = 21.53° and 2θ = 24.51°. These diffraction peaks are characteristic diffraction peaks of silicon dioxide, further indicating that silicon dioxide was generated after the hydrolysis and condensation of tetraethyl orthosilicate and vinyltrimethoxysilane.

[0090] 4. Differential Scanning Calorimetry (DSC) Test The DSC curve of the coated platinum catalyst provided in Example 1 was tested: the glass transition temperature of the polymer was determined by differential scanning calorimetry (DSC). 5-10 mg of coated platinum catalyst was weighed and placed in the sample cell. The heating range was -90℃ to 180℃, the heating rate was 20℃ / min, and the test was conducted under a nitrogen atmosphere.

[0091] Test results are as follows Figure 4 As shown, the prepared coated platinum catalyst has a melting point of around 62.5℃, which is about 10℃ higher than that of ordinary polycaprolactone diol (melting point around 52℃). The increased melting point helps to improve the thermal stability of the coated platinum catalyst, thereby extending its storage stability and preventing precipitation during storage, which would lead to a decrease in the extrusion rate of the thermally conductive gel and an increase in viscosity.

[0092] 5. Contact Angle Test The contact angle of the coated platinum catalyst provided in Example 1 was tested: The contact angle of the membrane surface was measured using a contact angle measuring instrument (SDC-200S) from Dongguan Shengding Precision Instruments Co., Ltd. 5 μL of water was used as the measuring liquid, and the contact angle at 3 locations was measured and the average value was taken.

[0093] 6. Stability Test The stability of the thermally conductive gels using the coated platinum catalysts provided in Examples 1-5 and Comparative Examples 1-5 was tested, and the test indicators included: (1) Extrusion ratio test The extrusion rate of the thermally conductive gel was tested one week after it was placed at 40°C.

[0094] (2) Viscosity test The initial viscosity and viscosity after 180 days were tested using a rotational viscometer.

[0095] (3) Anti-precipitation test After the thermally conductive gel is heated and cured, it is placed at 50°C for one week. Observe whether the surface becomes sticky or impurities are precipitated.

[0096] (4) Thermal conductivity test The thermal conductivity of thermally conductive gels shall be determined in accordance with GB / T 29313-2012.

[0097] The test results are shown in Table 1 below: Table 1 The test results above show that the thermally conductive gels prepared using the coated platinum catalysts provided in Examples 1-5 of this application all exhibit excellent physical properties: 1. Good storage stability: the initial viscosity and viscosity increase after 180 days are much smaller than those of the comparative sample, indicating that the catalyst is fully coated and leaks very little during long-term storage.

[0098] 2. Excellent retention: After being placed at 40℃ for one week, the extrusion rate decreased slowly, indicating that the system maintains good fluidity and has a long service life.

[0099] 3. Outstanding anti-precipitation performance: No precipitation occurred after high-temperature aging following curing, proving that the chemical bonding between the vinyl group on the shell surface and the matrix effectively prevented the migration and detachment of microspheres.

[0100] 4. Good thermal conductivity: Due to the use of highly thermally conductive modified nano zinc oxide as an emulsifier and the optimization of the shell composition, its negative impact on the overall thermal conductivity network is small, and its thermal conductivity is significantly better than that of the comparative example 2 using modified silica.

[0101] In summary, this application has successfully obtained a coated platinum catalyst with adjustable release temperature, good compatibility with the matrix, strong anti-precipitation properties, and stable storage through a specific organic-inorganic hybrid shell design and Pickering emulsion preparation process. It is particularly suitable for single-component high thermal conductivity gel systems with high reliability requirements.

[0102] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A coated platinum catalyst, characterized in that, include: The core material and a shell coating the core material are provided. The core material includes a Castiglione platinum catalyst and an inhibitor. The concentration of the Castiglione platinum catalyst in the coated platinum catalyst is 1000-5000 ppm, and the concentration of the inhibitor is 50-150 ppm. The shell coating is an organic-inorganic hybrid network, which is prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane.

2. The coated platinum catalyst according to claim 1, characterized in that, The organic-inorganic hybrid network is prepared by copolymerization of tetraethyl orthosilicate, polycaprolactone diol and vinyltrimethoxysilane in a mass ratio of 0.4:1:0.2-1:1:0.

4.

3. The coated platinum catalyst according to claim 2, characterized in that, The Castel platinum catalyst is a complex of platinum and tetramethyldivinyldisiloxane; the inhibitor is any one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, and 3,5-dimethyl-1-hexyn-3-ol.

4. The coated platinum catalyst according to claim 3, characterized in that, The number-average molecular weight of the polycaprolactone diol is 500-2000 g / mol.

5. A method for preparing the coated platinum catalyst as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Oil Phase Preparation: Under nitrogen protection, polycaprolactone diol is dissolved in petroleum ether at a mass ratio of 0.05:1 to 0.5:

1. The solution is heated to 50-60°C and stirred until dissolved. After cooling to 20-30°C, a caster platinum catalyst, an inhibitor, tetraethyl orthosilicate, and vinyltrimethoxysilane are added. The mass ratio of the caster platinum catalyst to the inhibitor is 20:1 to 50:1; the mass ratio of the caster platinum catalyst to tetraethyl orthosilicate is 1:0.2 to 1:1; and the mass ratio of polycaprolactone diol: tetraethyl orthosilicate: vinyltrimethoxysilane is 0.4:1:0.2 to 1:1:0.

4. The solution is stirred until homogeneous to obtain the oil phase. S2. Aqueous phase preparation: Modified nano zinc oxide is dispersed in deionized water, wherein the mass ratio of modified nano zinc oxide to deionized water is 0.005:1-0.02:1, and the pH value is adjusted to 5-6.5 to obtain the aqueous phase. S3. Preparation of Pickering emulsion: The oil phase is added to the aqueous phase at a speed of 6000-15000 rpm and reacted for 3-10 min to form an oil-in-water Pickering emulsion, wherein the mass ratio of the oil phase to the aqueous phase is 1:5-1:

20. S4. Interfacial polymerization coating: An organotin catalyst is added to the Pickering emulsion, the amount of which is 0.01-0.03% of the mass of the oil phase. The mixture is stirred at 30-45°C for 12-36 hours at a stirring speed of 200-800 rpm, so that tetraethyl orthosilicate, polycaprolactone diol, and vinyltrimethoxysilane in the oil phase undergo a co-condensation reaction at the oil-water interface to form a preproduct of an organic-inorganic hybrid network shell coating the core material. S5. Post-processing: The preproduct is centrifuged, washed, and dried to obtain the coated platinum catalyst.

6. The method for preparing the coated platinum catalyst according to claim 5, characterized in that, In step S2, the modified nano-zinc oxide is prepared through the following steps: Disperse 3-8 parts by mass of nano zinc oxide in a mixed solution consisting of 80-95 parts by mass of ethanol and 5-20 parts by mass of water to obtain a premix. Add 0.3-0.8 parts by mass of vinyltrimethoxysilane to the premix and adjust the pH to 3-5. React at 60-80°C for 6-10 hours. Centrifuge, wash, and dry the product obtained from the reaction to obtain modified nano zinc oxide.

7. The method for preparing the coated platinum catalyst according to claim 6, characterized in that, The particle size of the nano zinc oxide is 10-100 nm.

8. The method for preparing the coated platinum catalyst according to claim 5, characterized in that, The organotin catalyst is at least one of dibutyltin dilaurate, stannous octoate, or dibutyltin diacetate; in step S5, the preproduct is centrifuged at 5000-10000 rpm for 10-30 min, washed 2-5 times with methanol, then washed 2-5 times with petroleum ether, and finally washed 1-2 times with octamethylcyclotetrasiloxane. After washing, it is vacuum dried at 25-40℃ for 12-24 hours.

9. The application of a coated platinum catalyst as described in any one of claims 1-4 in a single-component thermally conductive gel, characterized in that, The single-component thermally conductive gel is prepared by the following steps: After mixing 86-90 parts by weight of thermally conductive filler, 6-9.6 parts by weight of vinyl silicone oil, 0.1-0.3 parts by weight of the coated platinum catalyst, and 0.8-1.5 parts by weight of silane coupling agent evenly, 1.2-2.4 parts by weight of side-chain hydrogen-containing silicone oil and 0.6-1.0 parts by weight of double-ended hydrogen-containing silicone oil are added, and the mixture is stirred and mixed. After vacuum degassing, a single-component thermally conductive gel is obtained.

10. The application according to claim 9, characterized in that, The thermally conductive filler is composed of a mixture of zinc oxide with a particle size of 30-50 nm, aluminum oxide with a particle size of 2-3 μm, and aluminum oxide with a particle size of 15-20 μm, wherein the mass ratio of zinc oxide with a particle size of 30-50 nm, aluminum oxide with a particle size of 2-3 μm, and aluminum oxide with a particle size of 15-20 μm is 1:2:7-1:3:6; the vinyl silicone oil has a viscosity of 1000-8000 mPa·s and a vinyl content of 0.16-2.5%; the silane coupling agent is one of decyltrimethoxysilane, dodecanetrimethoxysilane, or hexadecanetrimethoxysilane; the side-chain hydrogen-containing silicone oil has a viscosity of 20-100 mPa·s and a hydrogen content of 0.1-1.2%; the double-ended hydrogen-containing silicone oil has a viscosity of 20-40 mPa·s and a hydrogen content of 0.04-0.19%.

Citation Information

Patent Citations

  • Microencapsulated platinum catalyst and preparation method thereof

    CN104371106A

  • Capsule type platinum catalyst as well as preparation method and application thereof

    CN118788386A

  • Post-curing-free platinum catalyst raw rubber and preparation method thereof

    CN119859414A